Simulation of DC-DC converter considering parasitic element in flyback transformer and its effect on the converter's input current - Yaakub, Muhamad Faizal; Mohd Radzi, Mohd Amran; Mohd Noh, Faridah Hanim (2023)
The flyback converter presents itself as a compelling choice for DC-DC conversion in a wide range of applications, owing to the appealing advantages it offers. However, the overall performance of the converter is negatively impacted by parasitic components present in the transformer and converter circuits. The input current's quality has also been impacted by the switching frequency. The simulation based on flyback transformer 6-C modeling is presented in this study, with a particular emphasis on the input current of the converter using PSIM simulation software. It is evident that the input current of the converter becomes distorted with a high-frequency signal up to 2.5 MHz when the transformer enters its natural capacitive mode. Moreover, it should be noted that the conversion efficiency exhibits a decrease with an increase in the switching frequency. This analysis offers potential insights for enhancing converter design by taking into account the influence of parasitic elements.